Instrumen Hedging dan Solusinya Menurut Syariah - Oni Sahroni; Hasanuddin Hasanuddin; Cecep Maskanul Hakim (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2016)
Hedging Instrument and the Solution According to Sharia. Hedging (Hedging/ al-Tahawuth) is a method or technique to reduce the risks incurred or expected to be incurred as a result of price fluctuations in the financial markets. Hedging which is commonly used in conventional banking now could also be used in Islamic banking system, because the option contract is forbidden it contains gharar (speculation), like wise forward contract is also not allowed because it contains riba al-yad. Forward and Swaf contract is forbidden because it is an instrument of ash-Sharf al-ajil and ghara (khathar / speculation). Then the solution is through trading of currency with muwa’adah and selling foreign currency through commodity exchanges